Effective NiO channel engineering for performance enhancement of lateral perovskite-based UV photodetectors - Nguyen, Thi My Huyen; Tran, Manh Hoang; Dang, Xuan Du (Hue University Journal of Science: Natural Science, 2026)
Lateral perovskite-based ultraviolet photodetectors (UV PDs) are attractive for their simple fabrication and easy integration, but their performance is often limited owing to nonuniform film formation on patterned substrates and trap-assisted recombination during lateral charge transport. In this paper, a 70 nm sputtered NiO thin film is introduced as an interfacial channel layer prior to solution processing of halide perovskite on patterned ITO/glass with a 1 mm electrode gap. The NiO underlayer provides a crystalline wide-bandgap platform that improves perovskite film uniformity and promotes larger grains with fewer grain boundaries. Photoluminescence quenching and electrochemical impedance spectroscopy techniques further indicate reduced recombination and lower charge-transfer resistance, which is consistent with enhanced hole transport in the NiO-assisted architecture. Consequently, the NiO-integrated device exhibits a markedly increased photocurrent (0.476 to 1.28 µA at 370.92 µW/cm2 under 254 nm illumination), together with improved responsivity (17.4 to 33.04 mA/W) and EQE (8.5% to 16.2%). These results demonstrate that sputtered NiO serves as an effective interfacial channel to simultaneously improve film formation and charge extraction in lateral perovskite UV photodetectors.